Dogmática sobre a fundamentação analítica no CPC/2015: das decisões às postulações. - Castro, Lauro Alves de (2018)
The purpose of this paper is to examine whether there is a burden of analytical reasoning directed to the submissions of the parties in the context of CPC/2015, based on the approach on how the fundamental norm inserted in art. 6º, of CPC / 2015, that positive the principle of cooperation, and the standardization of minimum requirements for drawing up reasoned decisions, as provided in paragraphs 1 and 2 of art. 489 of CPC/2015, influence the form of application of the parties and impact on the construction of jurisdictional pronouncements. Therefore, apart from the definition of procedural cooperation and its impact on the issue s addressed, from the development on the duty to motivate judicial decisions in Brazil, and from the exposition of the current requirements in the applications of the parties, the study starts from a reality already materialized in the ordinated by precedents of the Superior Court of Justice, in which an extensive interpretation of art. 489, § 1º, of CPC/2015, which represents the duty of analytical justification of judicial decisions, directed to magistrates, to the applications of the parties. Consequently, the legal consequences of a poorly articulated postulation, which does not represent an analytical basis, and whether there is a possibility of amendment or supplementation of those applications, will be investigated when the magistrates find that there is a deficiency in the legal arguments put forward by the parties. In order to make the approach more concise and dogmatic, the research will count on the subsumption to the bibliographical and jurisprudential review on the subject and will be based on positive law, specifically relating to the subject, the following provisions of the new CPC: Articles articles 6º, 319, III, 321, 330, I, §§ 2º e 3º, 336, 489, §§ 1º e 2º, 525, §§ 4º e 5º, 550, §§ 1º e 3º, 917, §§ 3º e 4º 932, III, 932, sole paragraph, e 966, § 6º; which represent, in practice, an indispensable part of the problem, which may influence the way the parties formulate their applications in the context of the new Brazilian civil process code.